If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 15x Solving 22 = 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 22 + -15x = 15x + -15x Combine like terms: 15x + -15x = 0 22 + -15x = 0 Add '-22' to each side of the equation. 22 + -22 + -15x = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -15x = 0 + -22 -15x = 0 + -22 Combine like terms: 0 + -22 = -22 -15x = -22 Divide each side by '-15'. x = 1.466666667 Simplifying x = 1.466666667
| 25-5= | | -0.003x^2+0.577x+2=0 | | 67x-45y=56x+8y | | 6x^2-19x=14 | | 219-5x=31x+19 | | m^2-10m+18=0 | | 9+-8x=32+-15x | | 11x-19=6x+11 | | 2-(6-2x)=0 | | 12x-15y=80 | | 2x^4-9*x^3-4x^2-5x=0 | | x*3+x^2-8*x-8=0 | | 7y-5=3x+23 | | 4(x+1)-3(x-3)=25 | | -7x+3x^2+2=0 | | (x+4)2=81 | | 137=x+y | | 10x+12=112 | | -3x^2-2x+4=0 | | 4x+62=9x-13 | | 30-6x=3x+18 | | 10-6x=3x+18 | | =4x+15 | | -35-3x=9x+19 | | 130=2x-y | | -2(x+9)+91=13+24 | | 2(111)=d | | 7x+26=4x+77 | | 4x-6x=7 | | 34-2x=7x+21 | | -3x^2-4x+1=0 | | 3-8s=-29 |